2013
DOI: 10.1128/jvi.01813-13
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein (CRP) Is Essential for Efficient Systemic Transduction of Recombinant Adeno-Associated Virus Vector 1 (rAAV-1) and rAAV-6 in Mice

Abstract: eThe clinical relevance of gene therapy using the recombinant adeno-associated virus (rAAV) vectors often requires widespread distribution of the vector, and in this case, systemic delivery is the optimal route of administration. Humoral blood factors, such as antibodies or complement, are the first barriers met by the vectors administered systemically. We have found that other blood proteins, galectin 3 binding protein (G3BP) and C-reactive protein (CRP), can interact with different AAV serotypes in a species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 53 publications
0
30
0
Order By: Relevance
“…While even low-titer NAbs are associated with efficient vector neutralization in vivo (44)(45)(46), the presence of binding non-NAbs appear to enhance rAAV transduction efficacy, at least in some tissues (43). Pre-existing anti-AAV antibodies in individuals receiving rAAV vectors are being investigated as a potential source of toxicity related to complement activation (47) although a direct interaction of rAAV vectors with complement proteins was also reported (48,49).…”
Section: Humoral Immunity To Aavmentioning
confidence: 99%
“…While even low-titer NAbs are associated with efficient vector neutralization in vivo (44)(45)(46), the presence of binding non-NAbs appear to enhance rAAV transduction efficacy, at least in some tissues (43). Pre-existing anti-AAV antibodies in individuals receiving rAAV vectors are being investigated as a potential source of toxicity related to complement activation (47) although a direct interaction of rAAV vectors with complement proteins was also reported (48,49).…”
Section: Humoral Immunity To Aavmentioning
confidence: 99%
“…Inactivation by pre-existing neutralizing antibodies has been well documented. Recently, Denard et al found that some blood proteins bind to certain AAV serotypes in a species-specific manner [92,93]. In particular, AAV-6 interacts with the galectin 3 binding protein in human and dog sera but not macaque and mouse sera.…”
Section: Mechanistic Insights Of Systemic Aav Deliverymentioning
confidence: 99%
“…On the other side, AAV-6 interacts with the C-reactive protein in mouse but not human sera. Instead of inhibition, this interaction boosts systemic delivery [93]. …”
Section: Mechanistic Insights Of Systemic Aav Deliverymentioning
confidence: 99%
“…Interestingly, both AAV1 and AAV6 do not interact with murine or macaque G3BP. Further, both AAV strains have been shown to bind murine C-reactive protein, but not the human counterpart (Denard et al, 2013). These findings highlight the potential for variability in species-specific interactions between AAV capsids and host proteins in general.…”
Section: Aav6mentioning
confidence: 88%